2017
DOI: 10.1111/cyt.12505
|View full text |Cite
|
Sign up to set email alerts
|

The Paris System for urine cytology in upper tract urothelial specimens: A comparative analysis with biopsy and surgical resection

Abstract: More than one-third of the UUT cytological cases were classified as AUC and approximately 1/15 as suspicious or positive for HGUC. Based on UUT cytology specimens, the risk of malignancy of each cytological diagnostic category of TPS was comparable to those reported in the literature. The use of TPS in evaluating UUT cytology specimens was specific and sensitive in identifying patients with HGUC by histology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 24 publications
2
34
1
Order By: Relevance
“…After TPS implementation, the rate of HGUC increased from 7.3% to 13.0%, the sensitivity increased from 68% to 95%, the negative predictive value increased from 46% to 86%, and the diagnostic accuracy increased from 70% to 86% . Many other studies have reported better performance using TPS, with rare exceptions …”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…After TPS implementation, the rate of HGUC increased from 7.3% to 13.0%, the sensitivity increased from 68% to 95%, the negative predictive value increased from 46% to 86%, and the diagnostic accuracy increased from 70% to 86% . Many other studies have reported better performance using TPS, with rare exceptions …”
Section: Discussionmentioning
confidence: 94%
“…Currently, many laboratories across the world are implementing TPS. To gauge the efficacy of TPS for diagnosing and reporting urinary cytological samples, numerous articles have retrospectively evaluated the performance of PD against prior methodology …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of TPS diagnostic criteria resulted in a slightly increased use of the suspicious diagnostic category (26% to 36%) with no significant change in the diagnostic rate of the atypical diagnostic category. Zheng et al, also evaluated the effect of utilizing TPS in 125 upper urinary tract urine cytology specimens from 74 patients who had subsequent biopsies or resections within 2 months of upper urinary tract urine collection. In this study, the diagnostic rates in this cohort for non‐diagnostic, negative for HGUC, atypical urothelial cells, low‐grade urothelial neoplasm, suspicious for HGUC, and positive for HGUC were 1.6%, 39.2%, 17.6%, 8.8%, 16.8%, and 16%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This system primarily focuses on the detection of high‐grade urothelial carcinoma (HGUC) with a high sensitivity, followed by the detection of low‐grade urothelial neoplasm (LGUN) with a poor recognizing sensitivity . TPS further changes the uncharacteristic category into a reproducible and meaningful category, achieved by the inclusion of the cases having urothelial cells with nuclear atypia associated with HGUC, and exclusion of those with atypia associated with LGUN . So far, several studies have assessed the efficacy of TPS in urine cytology evaluations, in most of which TPS has been introduced as a reporting urine cytology template which has increased the detection rate of HGUC and reduced the rate of equivocal diagnoses .…”
Section: Introductionmentioning
confidence: 99%